2007
DOI: 10.1093/nar/gkm091
|View full text |Cite
|
Sign up to set email alerts
|

Novel protein fold discovered in the PabI family of restriction enzymes

Abstract: Although structures of many DNA-binding proteins have been solved, they fall into a limited number of folds. Here, we describe an approach that led to the finding of a novel DNA-binding fold. Based on the behavior of Type II restriction–modification gene complexes as mobile elements, our earlier work identified a restriction enzyme, R.PabI, and its cognate modification enzyme in Pyrococcus abyssi through comparison of closely related genomes. While the modification methyltransferase was easily recognized, R.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 44 publications
3
76
0
Order By: Relevance
“…Nonetheless, bioinformatics and biochemical analyses revealed that some type II REases possess unrelated catalytic domains from different nuclease superfamilies, including PLD, HNH, GIY-YIG, and half-pipe (reviewed in reference 8). These findings have been recently highlighted by crystal structures of Mg 2ϩ -independent enzymes: PLD-like R.BfiI (20) and half-pipe R.PabI (38).…”
mentioning
confidence: 79%
“…Nonetheless, bioinformatics and biochemical analyses revealed that some type II REases possess unrelated catalytic domains from different nuclease superfamilies, including PLD, HNH, GIY-YIG, and half-pipe (reviewed in reference 8). These findings have been recently highlighted by crystal structures of Mg 2ϩ -independent enzymes: PLD-like R.BfiI (20) and half-pipe R.PabI (38).…”
mentioning
confidence: 79%
“…A vast number of REases, with the exception of BfiI and PabI, show an absolute requirement for Mg 2ϩ for DNA cleavage (8,9). Other divalent ions with similar atomic radii are a poor replacement at the catalytic center.…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%
“…Generally, type II REases are homodimeric or homotetrameric and cleave DNA within or near their target site. These enzymes are highly diverse and are known to utilize at least five types of folds: PD-(D/E)XK, PLD, HNH, GIY-YIG, and halfpipe, e.g., R.EcoRI, R.BfiI, R.KpnI, R.Eco29kI, and R.PabI enzymes, respectively (2,(7)(8)(9)(10). Type II enzymes are the most widely studied and are also extensively utilized nucleases in genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Other type II restriction enzymes belong to the phospholipase D (PLD) superfamily, the HNH superfamily and the GIY-YIG superfamily [6][7][8][9][10] . In addition to these restriction enzyme superfamilies, we found a half-pipe superfamily for which R.PabI from the hyperthermophilic archaea Pyrococcus abyssi is representative 11,12 . There is no protein with a structure similar to the overall fold of R.PabI 12 .…”
mentioning
confidence: 99%
“…In addition to these restriction enzyme superfamilies, we found a half-pipe superfamily for which R.PabI from the hyperthermophilic archaea Pyrococcus abyssi is representative 11,12 . There is no protein with a structure similar to the overall fold of R.PabI 12 .…”
mentioning
confidence: 99%